Colour and the optical properties of materials - Tilley, R. J. D. (Wiley, 2020)
"This textbook focuses its attention upon the ways that colour can be produced and how these ways govern device applications. The first chapter introduces the notions of light as rays, waves or photons and its interaction with matter. The following chapters explain optical phenomena mostly in terms of light waves, covering colour due to refraction, dispersion, reflection, and scattering. The remaining chapters address colour production in terms of light as photons. This third edition: Retains the proven concept of the previous editions has been completely revised and updated Contains new and improved sections on photonic crystals, holograms, flat lenses, colour centres"